Latihan Pernapasan dalam Meningkatkan Kontrol Asma dan Kualitas Hidup Pasien Asma Dewasa - Eugenia Maria da Silva; Yulis Setiya Dewi; Eka Mishbahatul Mar’ah; Hasanudin Hasanudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of breathing exercises in improving asthma control and quality of life in adult asthma patients. The research method used was a systematic review with a randomized controlled trial (RCT) design. Searching for articles uses four databases, namely: CINAHL, PubMed, SAGE, and Scopus, from 1 September 2017 to 28 February 2021. The research results were 239 articles, 11 of which met the criteria. Breathing exercises given to asthma patients vary from breathing exercises carried out as a single intervention or combined intervention. Breathing exercises for asthma patients include yoga, inspiratory muscle exercises, progressive muscle relaxation, diaphragmatic breathing, slow breathing, and controlled breath holding. This intervention is a type of breathing exercise that significantly affects asthma control and the quality of life of asthma patients. In conclusion, breathing exercises are a non-pharmacological therapy that can be used in clinical practice to help patients manage asthma control and improve their quality of life in addition to pharmacological treatment. Keywords: Asthma Control, Quality of Life, Breathing Exercises, Yoga